Development of Game Application-Based Education Towards Adolescents' Knowledge Level: Mixed Methods - Devangga Darma Karingga; Achmad Wahdi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetes mellitus (DM) is a chronic disease whose prevalence continues to increase, including in adolescents. Knowledge about DM prevention in adolescents remains low, so innovative and engaging educational media are needed. This study aims to evaluate the effectiveness of educational games based on crossword puzzles and word searches in increasing the knowledge of adolescents at risk of DM. The study employed a Research and Development (R&D) design, comprising stages of application design, expert validation, and limited trials, conducted on 35 adolescents aged 12–18 years using purposive sampling. Community nurses and psychiatric nurses carried out validation. Knowledge was measured using the Diabetes Knowledge Questionnaire-24 (DKQ-24) through pre-test and post-test, and then analysed using the Wilcoxon Signed-Rank Test. The results showed a significant increase in knowledge scores from 11.0 ± 1.8 in the pre-test to 18.4 ± 1.7 in the post-test (p < 0.05). Expert validation confirmed that the application is suitable for use as an educational medium, with satisfaction scores > 4.0 in most aspects. Respondents found the game to be interactive, fun, and helpful in understanding important concepts related to diabetes, although some felt that the difficulty level needed adjustment. This educational game effectively increases the knowledge of adolescents at risk of diabetes and has the potential to be integrated into adolescent health promotion programs. Interactive technology-based media can serve as an engaging educational alternative, supporting community efforts to prevent diabetes.